In This Issue - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2008)
This issue of JMDE begins with associate editor Margaret Richardson's review of JMDE's first five years of publication in her paper titled "JMDE-Five Years in Review." In this paper, Richardson summarizes some of the key themes and content published in JMDE for the past five years and attempts to set the tone for the next five years.